A mechanistic insight into the mechanical role of the stratum corneum during stretching and compression of the skin. (September 2015) - Leyva-Mendivil, Maria F.; Page, Anton; Bressloff, Neil W.; Limbert, Georges
Abstract: The study of skin biophysics has largely been driven by consumer goods, biomedical and cosmetic industries which aim to design products that efficiently interact with the skin and/or modify its biophysical properties for health or cosmetic benefits. The skin is a hierarchical biological structure featuring several layers with their own distinct geometry and mechanical properties. Up to now, no computational models of the skin have simultaneously accounted for these geometrical and material characteristics to study their complex biomechanical interactions under particular macroscopic deformation modes. The goal of this study was, therefore, to develop a robust methodology combining histological sections of human skin, image-processing and finite element techniques to address fundamental questions about skin mechanics and, more particularly, about how macroscopic strains are transmitted and modulated through the epidermis and dermis. The work hypothesis was that, as skin deforms under macroscopic loads, the stratum corneum does not experience significant strains but rather folds/unfolds during skin extension/compression. A sample of fresh human mid-back skin was processed for wax histology. Sections were stained and photographed by optical microscopy. The multiple images were stitched together to produce a larger region of interest and segmented to extract the geometry of the stratum corneum, viable epidermis and dermis. From the segmented structures a 2D finite element mesh of the skin composite model was created and geometrically non-linear plane-strain finite element analyses were conducted to study the sensitivity of the model to variations in mechanical properties. The hybrid experimental-computational methodology has offered valuable insights into the simulated mechanics of the skin, and that of the stratum corneum in particular, by providing qualitative and quantitative information on strain magnitude and distribution. Through a complex non-linear interplay, the geometry and mechanical characteristics of the skin layers (and their relative balance), play a critical role in conditioning the skin mechanical response to macroscopic in-plane compression and extension. Topographical features of the skin surface such as furrows were shown to act as an efficient means to deflect, convert and redistribute strain—and so stress—within the stratum corneum, viable epidermis and dermis. Strain reduction and amplification phenomena were also observed and quantified. Despite the small thickness of the stratum corneum, its Young׳s modulus has a significant effect not only on the strain magnitude and directions within the stratum corneum layer but also on those of the underlying layers. This effect is reflected in the deformed shape of the skin surface in simulated compression and extension and is intrinsically linked to the rather complex geometrical characteristics of each skin layer. Moreover, if the Young׳s modulus of the viable epidermis is assumed to be reduced by a factor 12, the area of skin folding is likely to increase under skin compression. These results should be considered in the light of published computational models of the skin which, up to now, have ignored these characteristics. Graphical abstract: